Mechanistic DNA damage simulations in Geant4-DNA part 1: A parameter study in a simplified geometry. (April 2018) - Lampe, Nathanael; Karamitros, Mathieu; Breton, Vincent; Brown, Jeremy M.C.; Kyriakou, Ioanna; Sakata, Dousatsu; Sarramia, David; Incerti, Sébastien
Highlights: We explore parameters for mechanistically modelling DNA damage in a simple geometry. Simulations are run using a versatile simulations framework implemented in Geant4-DNA. We show different physics models can double the amount of DNA damage. We produce a set of parameters that replicates past simulations using Geant4-DNA. Abstract: Mechanistic modelling of DNA damage in Monte Carlo simulations is highly sensitive to the parameters that define DNA damage. In this work, we use a simple testing geometry to investigate how different choices of physics models and damage model parameters can change the estimation of DNA damage in a mechanistic DNA damage simulation built in Geant4-DNA. The choice of physics model can lead to variations by up to a factor of two in the yield of physically induced strand breaks, and the parameters that determine scavenging, and physical and chemical single strand break induction can have even larger consequences. Using low energy electrons as primary particles, a variety of parameters are tested in this geometry in order to arrive at a parameter set consistent with past simulation studies. We find that the modelling of scavenging can play an important role in determining results, and speculate that high-scavenging regimes, where only chemical radicals within 1 nm of DNA are simulated, could provide a good means of testing mechanistic DNA simulations.